A new model of microcracks propagation in granite rock - Ghiasi, Vahed; Omar, Husaini; Md Yusoff, Zainuddin; Kim Huat, Bujang; Muniandy, Ratnasamy; Alias, Mohd Najmin (American-Eurasian Network for Scientific Information, 2010)
One of the most significant current discussions in legal and moral philosophy is a new model of microcracks propagation in granite rock. The objective of this research is to identify the parameter that controls the crack propagation and identification a model to show the microcracks propagation in granite rock. To conduct this research, the samples of granite rock was used. Laboratory test was conducted for this research was Uniaxial Compressive Test (UCT), Schmite hammer and microscopic study to detection more about Thin Section(TS) of granite rock. This model is based on laboratory and field investigation on weathered granite in tropical area.